The Rational Islamic Actor? Evidence from Islamic Banking - Seda Demiralp; Selva Demiralp (Koç University-TÜSİAD Economic Research Forum (ERF), 2014)
Islamic banks create an interest in their own right as a rising branch in financial intermediation, particularly in the post-crisis era. In addition, they also deserve the attention of the students of Islamism due to their possible connection with Islamic movements. Through a comparison of Islamic and conventional banking, we analyze the motivations and behavior of Islamic economic actors who determine the cash flow to Islamic banks. Our findings suggest that, in contrast to popular views that portray these actors as ideologues or financiers of radical Islam, they have pragmatic motivations and may adapt to liberal systems to seize economic incentives.
Keywords: 330